Robust Fabrication of Hybrid Lead‐Free Perovskite Pellets for Stable X‐ray Detectors with Low Detection Limit - Tie, Shujie; Zhao, Wei; Xin, Deyu; Zhang, Min; Long, Jidong; Chen, Qi; Zheng, Xiaojia; Zhu, Jianguo; Zhang, Wen‐Hua (Advanced materials (Weinheim), 2020)
X‐ray detectors are widely utilized in medical diagnostics and nondestructive product inspection. Halide perovskites are recently demonstrated as excellent candidates for direct X‐ray detection. However, it is still challenging to obtain high quality perovskites with millimeter‐thick over a large area for high performance, stable X‐ray detectors. Here, methylammonium bismuth iodide (MA3Bi2I9) polycrystalline pellets (PPs) are developed by a robust, cost effective, and scalable cold isostatic‐pressing for fabricating X‐ray detectors with low limit of detection (LoD) and superior operational stability. The MA3Bi2I9‐PPs possess a high resistivity of 2.28 × 1011 Ω cm and low dark carrier concentration of ≈107 cm−3, and balanced mobility of ≈2 cm2 V−1 s−1 for electrons and holes. These merits enable a sensitivity of 563 μC Gyair−1 cm−2, a detection efficiency of 28.8%, and an LoD of 9.3 nGyair s−1 for MA3Bi2I9‐PPs detectors, and the LoD is much lower than the dose rate required for X‐ray diagnostics used currently (5.5 μGyair s−1). In addition, the MA3Bi2I9‐PPs detectors work stably under high working bias field up to 2000 V cm−1 after sensing an integrated dose >320 Gyair with continuous X‐ray radiation, demonstrating its competitive advantage in practical application. These findings provide an approach to explore a new generation of low LoD, stable and green X‐ray detectors based on MA3Bi2I9‐PPs. MA3Bi2I9 polycrystalline pellets (PPs) are fabricated by the robust, cost‐effective, and scalable cold isostatic‐pressing approach, and X‐ray detectors based on MA3Bi2I9‐PPs reach a limit of detection (LoD) of 9.3 nGyair s−1. The low LoD of the X‐ray detectors can obviously decrease the radiation dose used, thereby reducing health risks in medical diagnostics and security screening.